Decision Support System for Selecting Candidate of Indonesia Smart University Card Scholarship (Kip-K) recipients at Islamic University of Kuantan Singingi - Helpi Nopriandi; Aprizal Aprizal; Sri Chairani (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2023)
Islamic University of Kuantan Singingi still selects students to receive Indonesia Smart University Card Scholarship (KIP -K) by looking at the registration documents of new students one by one. In such a system, it spends a lot of time on the selection and also the review of the registration documents of the new students is done by the selection team and the management of Islamic University of Kuantan Singingi, so there are many considerations in this selection. The results of the selection also did not produce a written report on the condition of the first-year students who received the Indonesia smart university Card (KIP -K) scholarship, so this type of system is no longer used effectively. The application of Fuzzy Multiple Attribute Decision Making (FMADM) method can help in determining the weights of the values in each criteria. Using the simple additive weighting method (SAW) makes it easier to add the weighting values for each criterion.